IDENTIFIKASI POTENSI & MASALAH DESA SIDOMULYO SEBAGAI UPAYA PENGEMBANGAN DESA WISATA DI KOTA BATU - Pamela Dinar Rahma; Rifky Aldila Primasworo (Universitas Tribhuwana Tunggadewi Malang, 2017)
Sidomulyo is one of the tourist village in Batu own icon in the form of decorative flower and cut flowers. Sidomulyo offer views expanse of flowers of various kinds and colors. This tourist village has been supported by various facilities including lodging, restaurants, to shops that sell souvenirs. Sidomulyo also quite strategic location, not far from the city center and is close to other tourist attractions in Kota Batu. Sidomulyo faced with the lack of the number of visitors who enjoy the beauty of the village, visitors or tourists are mostly just a quick stop just to buy flowers. The purpose of this study was to determine the potential and problems in the village Sidomulyo. The method used is descriptive and qualitative. The final result of this study is the potential and the problems associated with the Sidomulyo village owned tourist attraction, accessibility, tourism facilities, market potential, human resources, and information and promotion.